Pengaruh Label Halal, Komposisi Bahan Pangan Dan Religiusitas Terhadap Minat Beli Produk Mie Instan Indomie Di Kota Pekanbaru Menurut Ekonomi Islam - Melati Julia Roikhani (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to find out whether the Halal Label, Food Ingredient Composition and Religiosity have a partial and simultaneous effect on buying interest in Indomie instant noodle products in the city of Pekanbaru. It is hoped that from this research, producers and consumers will be more selective in consuming food that is clearly halal. The type of research used is quantitative research with a research approach included in the associative research type. Data sources come from primary data and secondary data with data collection methods using questionnaire techniques. The population of the research was the Muslim community of Pekanbaru, 832,115 people, with a research sample of 247 respondents. The data analysis technique used in this research is multiple linear regression analysis using the SPSS version 16.0 application, including Research Instrument Test (Validity Test and Reliability Test), Classical Assumption Test, Hypothesis Test (t Test). The results of the statistical analysis of the test show that partially the variables Halal Label (X1), Food Composition (X2) and Religiosity (X3) have a positive and significant influence on Purchase Intention (Y) of Indomie instant noodles products among the people of Pekanbaru city. Meanwhile, the results of simultaneous statistical analysis show that the variables Halal Label (X1), Food Composition (X2) and Religiosity (X3) have a significant effect on Purchase Interest (Y) of instant noodle products among the people of Pekanbaru City.